Digital strategy implementation: The role of individual entrepreneurial orientation and relational capital - Ritala Paavo; Baiyere Abayomi; Hughes Mathew; Kraus Sascha (Elsevier, 2022)
In transformational strategy contexts such as digitalization, the entrepreneurial behavior of the firm's employees is crucial. This study examines the role of employees' individual-level entrepreneurial orientation (IEO) in terms of proactiveness, risk-taking, and innovativeness, and their relational capital within the organization, on their performance in achieving organizations' digital strategy goals. We hypothesize that all IEO dimensions are positively associated with employees' digital strategy performance and that relational capital positively moderates the effect of proactiveness and risk-taking but negatively moderates the effect of innovativeness. The results of an intra-organizational survey of 166 employees at a medium-sized Northern European manufacturing firm provide partial support for our hypotheses. As part of the empirical design, we introduce a four-dimensional scale for organizational and individual digital strategy performance (Digital - Management, Infrastructure, Networking, and development - MIND). With this scale, we contrast the informants' self-assessment of their individual performance against their assessment of the overall organizational performance. Our study is one of the first to investigate IEO in a digital strategy context and provides implications for harnessing employees' entrepreneurial and innovative potential in digital transformation.